The nucleon-induced deuteron breakup process as a laboratory for chiral dynamics - Skibiński, Roman; Golak, Jacek; Witała, Henryk; Chahar, Vaibhav; Epelbaum, Evgeny; Nogga, Andreas; Soloviov, Volodymyr (Frontiers in Physics, 2023)
The nucleon induced deuteron breakup reaction is studied within the Faddeev approach at incoming nucleon laboratory energies 135 and 200 MeV. The chiral SMS potential developed up to N4LO+ supplemented by the N2LO three-nucleon interaction, is used. Our investigation is focused on determination of theoretical uncertainties of predicted cross section related to its dependence on the value of the regulator cut-off parameter. We also compare predictions based on the complete N2LO potential with ones based on the two-nucleon force upgraded to the N4LO+ order and augmented with the N2LO three-nucleon force. In addition we study three-nucleon force effects predicted by this model of interaction. Our systematic study covers the whole kinematically allowed phase space, however our main results are obtained when additional restrictions on energies and cross section values are imposed. In such a case we find the regulator cut-off dependence of the differential cross sections to be moderate at 135 MeV and much stronger at 200 MeV. For the latter energy it can amount up to 45% in specific kinematical configurations. Taking into account terms above N2LO in two-body interaction changes the cross section up to 20% (27%) at E=135 (200) MeV. Inclusion of the three-nucleon force leads to approx. 27% effects at both energies. We exemplify these dependencies on few examples of the exclusive cross section given in function of the S-curve arc-length.